Supraorbital Rim Syndrome: Definition, Surgical Treatment, and Outcomes for Frontal Headache. Issue 7 (July 2016) - Hagan, Robert R.; Fallucco, Michael A.; Janis, Jeffrey E.
Abstract : Background: Supraorbital rim syndrome (SORS) is a novel term attributed to a composite of anatomically defined peripheral nerve entrapment sites of the supraorbital rim region. The SORS term establishes a more consistent nomenclature to describe the constellation of frontal peripheral nerve entrapment sites causing frontal headache pain. In this article, we describe the anatomical features of SORS and evidence to support its successful treatment using the transpalpebral approach that allows direct vision of these sites and the intraconal space. Methods: A retrospective review of 276 patients who underwent nerve decompression or neurectomy procedures for frontal or occipital headache was performed. Of these, treatment of 96 patients involved frontal surgery, and 45 of these patients were pure SORS patients who underwent this specific frontal trigger site deactivation surgery only. All procedures involved direct surgical approach through the upper eyelid to address the nerves of the supraorbital rim at the bony rim and myofascial sites. Results: Preoperative and postoperative data from the Migraine Disability Assessment Questionnaire were analyzed with paired t test. After surgical intervention, Migraine Disability Assessment Questionnaire scores decreased significantly at 12 months postoperatively ( P < 0.0001). Conclusions: SORS describes the totality of compression sites both at the bony orbital rim and the corrugator myofascial unit for the supraorbital rim nerves. Proper diagnosis, full anatomical site knowledge, and complete decompression allow for consistent treatment. Furthermore, the direct, transpalpebral surgical approach provides significant benefit to allow complete decompression.